2022
DOI: 10.1007/s13218-021-00750-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mathematics Teachers’ Understanding of Computational Thinking

Abstract: Computational thinking (CT) is often regarded as providing a ‘soft start’ for later involvement with artificial intelligence and, hence, as a crucial twenty-first century skill. The introduction of CT in primary mathematics curricula puts many demands on teachers, and their understanding of CT in mathematics is key to its successful introduction. Inspired by an information ecology perspective, we investigate how four primary school teachers understand CT in mathematics and how they go ahead to include CT in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The proficient teacher problem turned out to be an essential challenge to solve. Based on the findings in this study, resource problems, one of which is teacher ability, were reported to be a problem in the research of Chan et al (2021), Van Borkulo et al (2021), Pörn et al (2021), andNordby et al (2022). This finding reinforces previous findings by Saidin et al (2021), which state that the challenges of implementing CT in the classroom are teachers' understanding of CT, teachers' lack of confidence in using CT, and teachers' lack of skills to implement CT.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The proficient teacher problem turned out to be an essential challenge to solve. Based on the findings in this study, resource problems, one of which is teacher ability, were reported to be a problem in the research of Chan et al (2021), Van Borkulo et al (2021), Pörn et al (2021), andNordby et al (2022). This finding reinforces previous findings by Saidin et al (2021), which state that the challenges of implementing CT in the classroom are teachers' understanding of CT, teachers' lack of confidence in using CT, and teachers' lack of skills to implement CT.…”
Section: Discussionsupporting
confidence: 85%
“…Challenges related to teacher readiness and education in implementing CT were reported by the research of Chan et al (2021), Van Borkulo et al (2021), Pörn et al (2021), and Nordby et al (2022). Teacher readiness is also associated with positive attitudes and a broad view of programming by teachers Pörn et al (2021).…”
Section: Ct Helps Students Solve Real Problems They Encountermentioning
confidence: 93%
“…This interpretation posits computational thinking as a skill that goes beyond computer science, as it represents a universally applicable attitude and skill set for all [8]. This skill can be added to every child's analytical ability from an early age, adopting a cross-cutting component in 21st century school curricula [11]. From this perspective, the integration of computer science into schools has two main objectives: to offer all students the possibility of accessing computer science and to improve the learning of subjects known as STEAM (Science, Technology, Engineering, Arts and Mathematics) [12] by making the contents more authentic and relevant [13] and helping students with learning to break down a task into simpler ones, formulating and testing hypotheses, exploring and investigating, relating knowledge and coming up with original ideas or solutions.…”
Section: Introductionmentioning
confidence: 99%